DIFFERENCES OF THE TENSIOMYOGRAPHY-DERIVED BICEPS FEMORIS MUSCLE CONTRACTION TIME AND DISPLACEMENT BETWEEN DIFFERENT AGE AND FITNESS GROUPS - Vidnjevič, Marko; Tasheva, Rumiana; Urbanc, Jure; Gašperin, Urška (Annales Kinesiologiae, 2017)
Introduction: The aim of this study was to compare tensiomyography-derived biceps femoris muscle (BF) contraction time (Tc) and maximal radial muscle displacement (Dm). Methods: Ninety male participants were divided into 3 age groups: young adults (YA; 23.7 ± 4.3 years), middle-aged adults (MA; 46.7 ± 5.6 years), and older adults (OA; 64.2 ± 6.5 years). Furthermore, the participants were divided in two physical activity groups – the sedentary and those who were regularly engaged in recreational sports activities (at least three times a week). Tensiomyography (TMG) method was used to measure the BF Dm and Tc during isometric single-twitch maximal contraction. Results: We found shorter Tc in active YA than sedentary YA (P = 0.001). Active YA had also shorter Tc than active OA (P = 0.046). Active YA had also lower Dm than sedentary YA (P = 0.031), while pooled YA has trend towards lower Dm than pooled MA (P = 0.073) and pooled OA (P = 0.120). Discussion and conclusions: TMG data indicates a transition towards higher slow-twitch muscle fibre type with age and sedentary lifestyle. Furthermore, TMG data also indicates a lower muscle tone with age and sedentary lifestyle. Data obtained with TMG can be used to assess muscle imbalances in human body, which may be of clinical importance. Key words: tensiomyography, biceps femoris, lifestyle, aging, sport